Los títeres para el desarrollo de la convivencia en los niños de inicial ii de la unidad educativa del milenio Bernardo Valdivieso de la ciudad de Loja, en el periodo 2019-2020. - Capa Contento, Jennifer Thalía (2021)
This research entitled: THE TÍTERES FOR THE DEVELOPMENT OF COEXISTENCE IN THE CHILDREN OF INITIAL II OF THE EDUCATIONAL UNIT OF THE MILENIO BERNARDO VALDIVIESO OF THE CITY OF LOJA, IN THE PERIOD 2019-2020, has as its general objective to improve the development of social skills in children of the initial level II through the use of puppets. The research was mixed type te and during development the methods were used: scientific, analytical-synthetic, deductive and descriptive, as a technique the survey with mixed questions and instruments the observation guide and a valuation scale, the selected sample was 22 children at the age of 3 to 5 years and 2 teachers. The initial dianestic revealed that 72% of those investigated were in the process of achieving adequate participation, interaction and respect for the rules within the classroom. Therefore, it was considered appropriate to develop the alternative proposal "My Best Friends the Puppets" with dynamic activities, once the intervention was completed the post test was applied presenting as results that 53% managed to improve the relationship in the classroom. It is concluded that the use of puppets optimizes the development of coexistence in children by being a tool that captures their attention by helping them to correct the difficulties that arise in the relationship with others